Analisa Hukum Multiakad pada Layanan Jasa Go-Food (Studi Kasus pada Go-Jek Cabang Pasuruan) - Syarifah Fatimah Alattas (Universitas Islam Lamongan, 2023)
In this current era, the world is experiencing tremendous progress in technology and innovation. The presence of Go-Food fiture in Go-Jek application as a beneficial digital platform is welcomed enthusiastically by the community. Moreover, there are some arguments related to the prohibition of hybrid-contracts which are used in Go-Food transaction. For this reason, this study aims at determining the contract scheme for Go-Food services at the Go-Jek Pasuruan branch and how the argumentations of several contemporary fiqh scholars regarding the hybrid-contract laws are. This study uses a descriptive-qualitative method with a field research and library research approach. As a result, researchers found that the Go-Food transaction scheme in Pasuruan regency used hybrid contracts namely wakalah bil ujrah – qardh. In addition, there are different opinions among fiqh scholars according to this issue. The different opinion (khilafiyah) between the scholars is a necessity and common thing in responding fiqh cases based on Al Quran and Hadits, including Go-Food transactions. In this case, the author chooses to be in line with the argumentation that allows the use of Go-Food services based on the arguments presented by the ulama and fatwas that have been issued by the MUI.